Perancangan User Experience pada Aplikasi Pembukuan UMKM berbasis Mobile menggunakan Metode Human Centered Design (Studi Kasus: Suto Architect) - Revino Datya Baventa; Agi Putra Kharisma; Fais Al Huda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Suto Architect is an SME that operates in designing a various building designs and construction development projects in accordance with previously designed designs. The problem with Suto Architect's business is that they can only save their project requirement's note manually. This resulted in evidence of the project requirement's notes which was often tucked away and hampered to record their financial notes of project. Therefore, Suto Architect needs a solution in the form of an application that can make it easier to record and store their project requirement's notes. This research will focus on designing the user experience of a note-type mobile application called SME Accountancy using the Human Centered Design approach. Human Centered Design was chosen because the approach prioritizes user needs, capabilities, and behavior. The results of this study are in the form of mockup which is tested to end users. Tests include usability testing and user experience testing. The results of usability testing on the effectiveness aspect are 87.55%, the efficiency aspect is 0.106 goals/sec, and the user satisfaction aspect is 5.958 if interpreted in the SEQ assessment including the easy category. Then the user experience test using the User Experience Questionnaire (UEQ) with the results of the clarity rating scale being categorized as above average, the attractiveness, efficiency, and novelty rating scale having good categories, and the accuracy and stimulation rating scale being categorized as excellent.